Business intelligence-centered software as the main driver to migrate from spreadsheet-based analytics - Rebelo, Tomás de Oliveira Saramago Brito (2023)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence